Contribution of kelp dashi liquid to sustainable maintenance of taste sensation and promotion of healthy eating in older adults throughout the umami-taste salivary reflex - Satoh-Kuriwada, Shizuko; Gotoh, Satoshi; Shoji, Noriaki; Uneyama, Hisayuki; Komai, Michio (Frontiers in Nutrition, 2024)
Introduction Taste decline, including taste loss in older adults, leads to malnutrition and frailty. In a super-aging society, improving taste decline and maintaining taste sensation are crucial for the wellbeing of older adults. Hyposalivation frequently affects older individuals and is the leading cause of taste decline in older adults. Treating taste decline, including taste loss, in older adults presents challenges due to the limited sustainable methods for increasing saliva production, except for drug therapy, which may lead to adverse effects. Umami-taste stimulation results in a prolonged increase in both the whole salivary flow rate (WF), more than 90% of which is secreted from the major salivary glands, and the minor salivary gland flow rate (MF) in healthy volunteers through the umami-taste salivary reflex. We hypothesized that umami-rich kelp dashi liquid (KDL), commonly used in Japanese cuisine, may alleviate taste decline and sustain normal taste sensation in older adults with hyposalivation. This study investigated whether KDL stimulation could improve taste decline. Materials and methods A non-randomized controlled trial was conducted at the dental department of a university hospital, involving those who presented with dry mouth between May 2017 and December 2021. Before and after repeated KDL stimulation, characteristics like changes in WF and MF, the recognition thresholds (RTs) for five basic tastes, and subjective eating and swallowing difficulties were assessed. Statistical comparisons were performed between the values measured before and after KDL stimulation. Result A total of 35 older patients were included. Patients with reduced MF and with or without reduced WF exhibited umami-taste loss. Repeated stimulation with KDL increased MF and WF and improved taste loss, including umami, decreased RTs, and normalized each taste. Furthermore, subjective taste impairment, subjective eating and swallowing difficulties, and burning sensations in the oral mucosa were alleviated. Conclusion These findings indicate that KDL stimulation improved umami-taste loss and normalized each taste sensation, further alleviating eating difficulties via the umami-taste salivary reflex. Importantly, umami-taste loss was also observed in patients with normal WF but decreased MF, who are typically not diagnosed with hyposalivation. Therefore, KDL has the potential to sustain taste sensations and promote healthy eating habits in older individuals.